Bright neodymium complexes for efficient near infra-red organic light emitting diodes. (11th August 2020) - Ahmed, Zubair; Avila, Harold C.; Carvalho, Rafael S.; Kai, Jiang; Resende, J. A. L. C.; Bandini, Elisa; Barbieri, Andrea; Cremona, Marco
Abstract : This paper reports the synthesis, structures, and photophysical and electroluminescence properties of low symmetry NIR emitting octa- and nona-coordinate Nd tris β-diketonate complexes. Abstract : This paper reports the synthesis, structures, photophysics and optoelectronics of three NIR-emitting ternary neodymium tris β-diketonate complexes, [Nd(hfpd)3 (L) n =1–2 (H2 O) x =0–2 ](H2 O) y =0–1 (hfpd = anionic form of 1, 1, 1, 5, 5, 5-hexafluoropentane-2, 4-dione; L = diphenyl sulfoxide (dpso), n = 1, x = 2, y = 1 (1 ); L = dibenzyl sulfoxide (dbso), n = 1, x = 1, y = 0 (2 ); L = triphenyl phosphine oxide (tppo), n = 2, x = 0, y = 0 (3 )). The complexes were used as active components in emitting layers to fabricate NIR-OLEDs with multilayered structures: ITO/MoO3 (2 nm)/β-NPB (30 nm)/TcTa:[Nd-complex] (20 nm)/TPBi:[Nd-complex] (10 nm)/TPBi (10 nm)/Alq3 (40 nm)/LiF (0.1 nm)/Al (100 nm). The performance of the present devices is on a par with the best Nd complex based devices reported so far.